Heat transition: Municipalities need federal support in decommissioning natural gas networks - Isabell Braunger; Philipp Herpich; Franziska Holz; Julia Rechlitz; Claudia Kemfert (DIW Weekly Report, 2024)
Large parts of the existing natural gas distribution networks must be decommissioned due to the decarbonization of the heat supply. However, there are neither regulatory nor economic incentives for the gas network operators to do so and delaying the decommissioning could be expensive for the remaining customers. This Weekly Report analyzes to what extent municipalities can partially decommission the natural gas infrastructure with the help of municipal heat planning and by re-municipalizing the gas industry. This study also outlines the challenges associated with these instruments. Accordingly, re-municipalization does not necessarily result in the gas networks being decommissioned faster, a fact that remains unconsidered in the existing heat plans. Furthermore, the current regulatory framework, which is based on cost efficiency and the obligation to connect, makes decommissioning more difficult. In addition, the municipalities have a financial incentive to continue generating revenue from gas, partially because alternative income sources for funding public services are unavailable. Thus, the regulation must be adjusted and the federal and state governments must provide more support for the municipalities in organizing the partial decommissioning of the natural gas infrastructure.
Keywords: L95; R53; Q48; 330; natural gas infrastructure; heat; infrastructure planning; stranded assets